2020
DOI: 10.1186/s13104-020-04957-y
|View full text |Cite
|
Sign up to set email alerts
|

On estimating the number of people with known HIV positive status

Abstract: Objective: In 2014, the Joint United Nations Program on HIV and AIDS (UNAIDS) and partners set the '90-90-90 targets' . Many countries are facing the challenge of estimating the first 90. Our objective was to propose an alternative modelling procedure, and to discuss its usefulness for taking into account duplication. Results:For deduplication, we identified two important ingredients: the probability for an HIV+ person of being re-tested during the period and average number of HIV+ tests. Other adjusted factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Among HIV-positive adults in EPHIA, 79% knew that they were HIV positive. This was similar to the awareness level estimated by another study in Ethiopia [20], but lower than the 2020 UNAIDS global estimate for eastern and southern Africa [4], which reported an awareness level of 87%. The PHIA surveys in several other countries [21] as well as other small-scale studies in Africa [22,23] showed that countries in the continent were at various stages of progress towards achieving the first 90 target.…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…Among HIV-positive adults in EPHIA, 79% knew that they were HIV positive. This was similar to the awareness level estimated by another study in Ethiopia [20], but lower than the 2020 UNAIDS global estimate for eastern and southern Africa [4], which reported an awareness level of 87%. The PHIA surveys in several other countries [21] as well as other small-scale studies in Africa [22,23] showed that countries in the continent were at various stages of progress towards achieving the first 90 target.…”
Section: Plos Onesupporting
confidence: 83%
“…The targets were widely promoted and adopted by countries and international implementing partners [3]. By 2020, though only a few countries had taken sufficient action to achieve the targets, much of the complex reality of the HIV epidemic was increasingly understood and countries were in a better position to identify gaps and develop strategies to reach PLHIV who were left behind [4]. A comprehensive approach would be required to fill the gaps and achieve the next set of UNAIDS 95-95-95 testing and treatment targets; 95% of people living with HIV know their HIV status, 95% of PLHIV who know their status are on treatment, and 95% of people on treatment have suppressed viral loads, thereby reducing the annual number of new HIV infections among adults to 200,000 or fewer; and achieving zero discrimination by 2030 [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Kingdom of Eswatini has made remarkable progress scaling up HIV testing, prevention, and treatment services. Although the country has among the world’s highest HIV prevalence, 26.8% among adults in 2021 [ 1 ], Eswatini was one of the first countries to achieve the UNAIDS 95-95-95 epidemic control goals [ 2 ] and has reduced HIV incidence from 2.4% in 2011 to 0.5% in 2020 [ 1 , 3 ]. Universal access to antiretroviral therapy (ART) is a cornerstone of the national HIV strategy, and the number of people on ART grew from approximately 60,000 in 2010 to over 200,000 in 2020 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%